2018
DOI: 10.1002/ccd.27570
|View full text |Cite
|
Sign up to set email alerts
|

Coronary physiological assessment combining fractional flow reserve and index of microcirculatory resistance in patients undergoing elective percutaneous coronary intervention with grey zone fractional flow reserve

Abstract: Worsening of physiological indices after PCI was not uncommon in territories showing grey-zone FFR. Physiological assessment combining FFR and IMR may help identify patients who may benefit by PCI, particularly those in the grey zone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…7 11 However, for lesions with FFR values in the range of 0.76 to 0.80, which is the so-called gray-zone (prevalence of 15%), 12 the optimal treatment strategy is still debatable. 13 16 In addition, although the FFR cutoff value of 0.80 is widely used for decision-making, its validity has only been investigated in a small study that compared it with a noninvasive stress test. 5 Therefore, the optimal revascularization threshold of FFR deserves further evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…7 11 However, for lesions with FFR values in the range of 0.76 to 0.80, which is the so-called gray-zone (prevalence of 15%), 12 the optimal treatment strategy is still debatable. 13 16 In addition, although the FFR cutoff value of 0.80 is widely used for decision-making, its validity has only been investigated in a small study that compared it with a noninvasive stress test. 5 Therefore, the optimal revascularization threshold of FFR deserves further evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for this are speculative; distal embolization and microvascular injury are only partly responsible. The data from Niida et al confirm and extend these early findings by demonstrating that those with the lowest initial FFR and CFR have the most to gain after PCI, while those with gray‐zone FFR had much less to gain in terms of flow after stenting.…”
mentioning
confidence: 63%
“…Niida et al, in this issue of Catheterization and Cardiovascular Interventions, add mechanistic detail to understanding the effects of PCI in the FFR gray zone. In this single‐center retrospective analysis, 296 patients with stable angina and a single coronary lesion had combined pressure and flow measurements before and after PCI.…”
mentioning
confidence: 99%
“…The changes of iFR among six situations of MR were within 0.05 in most branches except for those distal to the severe stenosis in Case 3. Comparatively, FFR value is sensitive to MR variation, therefore could not independently detect the decrease in blood flow after percutaneous coronary intervention (PCI) (23), (24). The fitting results of in-vivo measurement of 255 coronary arteries indicated that, with MR doubled from 1.5 to 3 mmHg.s/cm, the increase of FFR ranged between 0.03 to 0.15 even in cases with mild stenosis (<58% in diameter, <83% in area) (3).…”
Section: Discussionmentioning
confidence: 99%